KELUARGA PEMODERASI KETERAMPILAN DAN KEPERCAYAAN DIRI DALAM MENUMBUHKAN MINAT BERWIRAUSAHA ANGGOTA KARANG TARUNA DESA SIULAK KECIL KAB. KERINCI - Melifia Liantifa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is conducted to determine the moderating effect of family on the relationship between skill and self confidence on interest in entrepreneurship on youth organization members in Siulak Kecil, Kerinci Districts. The research of sample was all youth organization members in Siulak Kecil, Kerinci districts which accounted for 100 peoples from all populations 100 peoples with prabability 5% and using full sampling. Data was colected through questionnaire with likert’s scale which analysis using deskriptive qualitative and quantitative as test of validity and reliability, average score and TCR, classic assumption test, coefisien of determination, hypothesis testing performs moderated regression analysis (MRA) by processing the data using SPSS for windows. Based on the results of the study indicate that: skill has a positive and significant effect on interest in entrepreneurship 0,000 <0,05. Self Confidence has a positive and significant effect on interest in entrepreneurship 0.012> 0.05. The family has a positive and significant effect on interest in entrepreneurship 0.005 <0.05. The family as a moderating variable between skill on interest in entrepreneurship 0.022 <0.05. The Family as a moderating variable between Self Confidence on interest in entrepreneurship 0.010 <0.05